Job Satisfaction Mediate the Relationship Between Job Security, Organizational Justice and Organizational Productivity - Moeen Ul Haq; Muhammad Imran; Khan Bahadar; Muhammad Waqas Qazi (Journal of Management Practices, Humanities and Social Sciences, 2023)
Human resource management played an important role between employees and the organization by making the employees satisfied in their job. This research is quantitative in nature and a comprehensive questionnaire is used to collect the data from bank employees especially from middle managers. Total 123 questionnaires are distributed in which 100 are return complete fill. The response rate are 81% and the data is collected from rural district of KPK Swabi. The result of data illustrate that the employees have strong concern with organizational justice and job security which have ultimate impact on organizational productivity because when they are satisfy from their job it lead organization in positive direction. The analysis show if organization provides organizational justice and job security to their employees, it motivates employees and they work hard for the success of organization. The conclusion of this research helps private organizations to understand the most important needs of employees in shape of justice in organization and job security. Only those organizations can compete and survive in today tough market whose employees are satisfied from their job. And the result of this research shows that when employer provides organizational justice and job security to their employees, mostly they become satisfy. It means that organizational productivity is directly link with employees’ satisfaction